Design and Experimental Results of Battery Charging System for Microgrid System - Byunggyu Yu (International Journal of Photoenergy)
Nowadays, many countries have paid attention to renewable energy due to fossil fuel crisis and its related environmental pollution. In particular, following the government supply business for renewable energy industry, the private sectors drive the stable power supply by using renewable sources for both microgrid system and standalone application. Battery charging and discharging control system of microgrid system are critical to extend lifetime of standalone photovoltaic system. Corresponding to this demand, this paper presents the development of battery charging and discharging system based on battery modeling, SOC (state of charge) estimation, and its implementation for 5 kW. As a result, the conversion efficiency shows 96.35% with over 95% charging performance.